Relation between Color and Surface Morphology of Electrodeposited Chromium for Decorative Applications. Issue 6 (1st January 2019) - Leimbach, Martin; Tschaar, Christoph; Zapf, David; Kurniawan, Mario; Schmidt, Udo; Bund, Andreas
Abstract : Electrolytes for decorative chromium plating based on trivalent chromium salts are known since several decades. As the use of conventional, hexavalent chromium based plating baths is more and more restricted by governmental regulations, these electrolytes gain ground in electroplating industry. However, compared to hexavalent chromium electrolytes, trivalent chromium electrolytes cannot fully meet the requirements with regard to appearance of the electrodeposited chromium, and there is little knowledge about the influencing factors on the shade of color. In this paper, chromium plated from a solution of chromium(III) sulfate was characterized by colorimetry, SEM and AFM and compared to a sample plated from a chromic acid electrolyte in order to reveal correlations between visual appearance and surface morphology. A relation between an increase of grain size and a color shift from blueish to yellowish was observed. Unlike in hexavalent based systems, grain size, roughness and color depend on layer thickness as the grain growth mechanism appears to be different. A model based on the theory of light scattering at rough surfaces is provided that links roughness and reflection behavior of the chromium surface.